Híbridos e mutantes: estudo comparativo entre aconselhamento genético e eugenia - Bruno Lucas Saliba de Paula (2014)
This work aims to identify points of similarity and rupture between eugenics and genetic counselling. We analyse the contexts in which these practices occur, as well as their discourse and the peculiarities of how they operate. On the one hand, both base themselves on a regime of truth in which what is true and legitimates decision-making mainly emerges from science. Furthermore, features of the biopolitics related to eugenics e.g. State and individuals pursuing together the well being of the nation and the grounding of government policies and individual choices in a calculation based in costs and benefits are also important for genetic counselling. On the other hand, while eugenics was practiced by States that disciplined individual conduct and regulated their populations to improve the human race, genetic counselling emerged in a configuration of diminishing States duties. Health care is increasingly up to individuals, as well as the management of the risks that may afflict their lives. Government, market and experts solely modulate (eventually adopting punitive attitudes, when some flow is out of control) the probabilities and risks related to individuals who, as entrepreneurs of themselves, voluntarily manage their genetic capital. Thus, there is an affinity between the rationalities of genetic counselling, neoliberal governmentality and society of control. Nevertheless, besides producing processes of self-surveillance and self-regulation, neoliberalism opens opportunities to practice a new kind of citizenship, a biological or a genetic citizenship. It is experienced, for instance, by associations of patients with certain diseases, by deaf people who use genetics to have deaf children or by patients-costumers who, as stakeholders, increasingly engage themselves in demands for funding and improvements in the treatment of their diseases. This new kind of citizenship proves to be an important object of study because it shows potentialities in sociotechnical trajectories and because it allows us to identify the modes and the effects of the resistance to technocracy and representative democracy.